Measurement of inclusive charged-particle jet production in Au + Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert; Weidenkaff, Philipp (Physical review, 2020)
The STAR Collaboration at the Relativistic Heavy Ion Collider reports the first measurement of inclusive jet production in peripheral and central Au+Au collisions at √sNN=200 GeV. Jets are reconstructed with the anti-kT algorithm using charged tracks with pseudorapidity |η|<1.0 and transverse momentum 0.2<pchT,jet<30 GeV/c, with jet resolution parameter R=0.2, 0.3, and 0.4. The large background yield uncorrelated with the jet signal is observed to be dominated by statistical phase space, consistent with a previous coincidence measurement. This background is suppressed by requiring a high-transverse-momentum (high-pT) leading hadron in accepted jet candidates. The bias imposed by this requirement is assessed, and the pT region in which the bias is small is identified. Inclusive charged-particle jet distributions are reported in peripheral and central Au+Au collisions for 5<pchT,jet<25 GeV/c and 5<pchT,jet<30 GeV/c, respectively. The charged-particle jet inclusive yield is suppressed for central Au+Au collisions, compared to both the peripheral Au+Au yield from this measurement and to the pp yield calculated using the PYTHIA event generator. The magnitude of the suppression is consistent with that of inclusive hadron production at high pT and that of semi-inclusive recoil jet yield when expressed in terms of energy loss due to medium-induced energy transport. Comparison of inclusive charged-particle jet yields for different values of R exhibits no significant evidence for medium-induced broadening of the transverse jet profile for R <0.4 in central Au+Au collisions. The measured distributions are consistent with theoretical model calculations that incorporate jet quenching.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 29.01.2021